Reproduction, health, and medicine - Armstrong, Elizabeth Mitchell; Markens, Susan; Waggoner, Miranda R. (Advances in medical sociology, 2019)
At a moment when reproduction is increasingly politicized, this volume explores the breadth of contemporary research on reproduction from the perspective of medical sociology, illuminating the lived experience of reproduction and offering insights to inform sociology and health policy. Reproduction, Health, and Medicine elucidates the tensions and contradictions between the normal physiologic processes of pregnancy and birth and the sociocultural beliefs, values, and arrangements that shape how we experience these biological phenomena. Investigating a range of reproductive events and experiences, including pregnancy, birth, abortion and fertility planning, the volume advances our understanding of how lay people and professionals make cultural meaning out of these processes in diverse settings. The chapters highlight how studies of reproduction, health, and medicine interface with core sociological concepts such as stratification, inequality, intersectionality, family and kinship, risk, and social control, and how experiences of reproduction are shaped by gender, race, class, sexuality and citizenship, as well as culture, health care systems, and health politics.